Thermodynamic processes on a semiconductor surface during in‐situ multi‐beam laser interference patterning. Issue 1 (1st February 2019) - Wang, Yun‐Ran; Jin, Chao‐Yuan; Ho, Chih‐Hua; Chen, Si; Francis, Henry; Hopkinson, Mark
Abstract : Laser interference has been widely used to produce one‐dimensional gratings and more recently has shown great potential for two‐dimensional patterning. In this study, the authors examine by simulation, its application to in‐situ patterning during materials growth. To understand the potential, it is important to study the surface processes resulting from the laser–matter interaction, which have a key influence on the resulting growth mechanisms. In this work, the intensity distribution and the laser–semiconductor interaction resulting from four‐beam interference patterns are analysed by numerical simulations. In particular, the authors derive the time and spatially dependent thermal distribution along with the thermal‐induced desorption and surface diffusion. The results provide a crucial understanding of the light‐induced thermal profile and show that the surface temperature and the surface adatom kinetics can be controlled by multi‐beam pulsed laser interference patterning due to photothermal reactions. The approach has potential as an in‐situ technique for the fast and precise nanostructuring of semiconductor material surfaces.